Impact of fermentation temperature on required heat dissipation, growth and viability of yeast, on sensory characteristics and on the formation of volatiles in Riesling. (27th February 2019) - Schwinn, M.; Durner, D.; Wacker, M.; Delgado, A.; Fischer, U.
Abstract: Background and Aims: Temperature control during fermentation significantly impacts the energy demand of wineries. We determined the heat required to be dissipated from wine tanks under three different temperature programs (14, 16–11–17 and 19°C) during 1200 L Riesling fermentations and investigated the influence of temperature on yeast growth and viability, the formation of yeast derived volatiles and wine sensory properties. Methods and Results: Heat dissipated by the coolant was determined using heat meters. At 19°C, ~70% less heat had to be dissipated compared to that at 14°C, whereas ~30% less heat had to be dissipated for the 16–11–17°C temperature program. The duration of fermentation was 15, 13 and 9 days for the 14, 16–11–17 and 19°C programs, respectively. Characteristic profiles of heat dissipated per day and reduction in specific gravity were observed. The formation of most esters was more pronounced in the second half of fermentation at higher temperature. Hexyl acetate, however, was formed early and no temperature influence was observed. The final concentration of ethyl decanoate, ethyl octanoate and ethyl hexanoate was greater for fermentations at 19°C, while that of ethyl butanoate was highest at 14°C. No difference was found in the final concentration of acetate esters or acetic acid. Acetaldehyde concentration was 35% lower for fermentations at 19°C, compared with those at 14°C. Descriptive analysis, at 5 and 11 months after bottling, revealed no significant difference in wine sensory profiles. Flow cytometry showed faster yeast growth, greater population size and rapid viability decline at the higher fermentation temperature. Conclusions: Energy savings can be achieved by reducing the required dissipated heat through temperature management of fermentations, without compromising wine composition. Ambient temperature should be considered when deciding on temperature management and related saving potentials. Significance of the Study: Potential energy savings were demonstrated that may facilitate innovation in fermentation cooling systems.